If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m + -37 = 49 Reorder the terms: -37 + m = 49 Solving -37 + m = 49 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '37' to each side of the equation. -37 + 37 + m = 49 + 37 Combine like terms: -37 + 37 = 0 0 + m = 49 + 37 m = 49 + 37 Combine like terms: 49 + 37 = 86 m = 86 Simplifying m = 86
| 44=h-33 | | 8/x=12/3 | | 8w-15w=35 | | 55=k-29 | | Y/3.5=10 | | 41=y+19 | | y-7=2.66(x-10) | | 4[4-(3-7x)]+2x=5(6x+3)-11 | | -1+2=2+3(2-1) | | 39+b=50 | | 3/8=x/1 | | c-3=13 | | 3(sin)x+1=(sin)x | | 10/1=x/2 | | 12x+9=8x+3+4x | | x+24=28 | | 62+5x=3(-x+3)-11 | | .09x+.11(x+9000)=2590 | | 2f=86 | | 33=-3f | | 2.5d+3.25=1+3.25 | | -7-13=9x+18-18x | | -70=7k | | 0=4/15y-28 | | 1/x=7/3 | | 7-8d=39 | | 1.08y=y+48 | | 3x-55+2x=5y | | Y+4.7=-8.6-5.3 | | -4x+6-5(x-1)=-(3x-3)-5x+5 | | X-0.2=6.4 | | 5x-2(3-4x)=3(x-3)-57 |